The Challenges of Detecting Circulating Tumor Cells in Sarcoma - Tellez-Gabriel, Marta; Brown, Hannah K.; Young, Robin; Heymann, Marie-Françoise; Heymann, Dominique (Frontiers in Oncology, 2016)
Sarcomas are a heterogenous group of malignant neoplasms of mesenchymal origin, many of which have a propensity to develop distant metastases. Cancer cells that have escaped from the primary tumour are able to invade into surrounding tissues, to intravasate into the bloodstream to become Circulating Tumour Cells (CTCs), and are responsible for the generation of distant metastases. Due to the rarity of these tumours and the absence of specific markers expressed by sarcoma tumour cells, the characterisation of sarcoma CTCs has to-date been relatively limited. Current techniques for isolating sarcoma CTCs are based on size criteria, the identification of circulating cells that express either common mesenchymal markers, sarcoma specific markers such as CD99, CD81 or PAX3, chromosomal translocations found in certain sarcoma subtypes such as EWS-FLI1 in Ewing’s sarcoma, detection of osteoblast-related genes, or measurement of the activity of specific metabolic enzymes. Further studies are needed to improve thee isolation and characterisation of sarcoma CTCs, to demonstrate their clinical significance as predictive and/or prognostic biomarkers, and to utilise CTCs as a tool for investigating the metastatic process in sarcoma and to identify novel therapeutic targets. The present review provides a short overview of the most recent literature on CTCs in sarcoma.